Effects of Octreotide–Long-Acting Release Added-on Tolvaptan in Patients with Autosomal Dominant Polycystic Kidney Disease: Pilot, Randomized, Placebo-Controlled, Cross-Over Trial. Issue 2 (February 2023) - Trillini, Matias; Caroli, Anna; Perico, Norberto; Remuzzi, Andrea; Brambilla, Paolo; Villa, Giulia; Perna, Annalisa; Peracchi, Tobia; Rubis, Nadia; Martinetti, Davide; Caruso, Mariarosa; Leone, Valentina Fanny; et al.
Visual Abstract: Abstract : Background: Tolvaptan and octreotide–long-acting release (LAR) have renoprotective effects in autosomal dominant polycystic kidney disease (ADPKD) that are partially mediated by amelioration of compensatory glomerular hyperfiltration. We compared the effects of tolvaptan and octreotide-LAR combination therapy versus those of tolvaptan monotherapy in patients with ADPKD. Methods: This pilot, randomized, placebo-controlled, cross-over trial primarily compared the effects of 1- and 4-week treatments with octreotide-LAR (two 20-mg i.m. injections) or placebo (two i.m. 0.9% saline solution injections) added-on tolvaptan (up to 90 and 30 mg/d) on GFR (iohexol plasma clearance) in 19 consenting patients with ADPKD referred to a clinical research center in Italy. Analyses were intention-to-treat. The local ethical committee approved the study. Results: At 4 weeks, GFR significantly decreased by a median (interquartile range) of 3 (−1 to 5) ml/min per 1.73 m 2 with tolvaptan and placebo ( P =0.01) and by 7 (3–14) ml/min per 1.73 m 2 with tolvaptan and octreotide-LAR ( P =0.03). GFR changes during the two treatment periods differed by 2 (−5 to 14) ml/min per 1.73 m 2 ( P =0.28). At 1 week, GFR significantly decreased by 3 (0–7) ml/min per 1.73 m 2 with tolvaptan and placebo ( P =0.006) and by 10 (−6 to 16) ml/min per 1.73 m 2 with tolvaptan and octreotide-LAR add-on therapy ( P <0.001). GFR changes during the two treatment periods significantly differed by 3 (0–12) ml/min per 1.73 m 2 ( P =0.012). Total kidney volume nonsignificantly changed by 4 (−48 to 23) ml with tolvaptan and placebo ( P =0.74), whereas it decreased significantly by 41 (25–77) ml with tolvaptan and octreotide-LAR ( P =0.001). Changes during the two treatment periods differed by 36 (0–65) ml ( P =0.01). Octreotide-LAR also attenuated ( P =0.02) the aquaretic effect of tolvaptan. Treatments were well tolerated. Conclusions: In patients with ADPKD, octreotide-LAR added-on tolvaptan reduced GFR more effectively than octreotide-LAR and placebo. Octreotide-LAR also reduced total and cystic kidney volumes and attenuated the acquaretic effect of tolvaptan. Clinical Trial registry name and registration number: Tolvaptan-Octreotide LAR Combination in ADPKD (TOOL), NCT03541447 .